Optimasi Kinerja Alat Fourier Transform Infrared (FTIR) Melaui Studi Perbandingan Komposisi dan Ketebalan Sampel-KBr - I Dewa Putu Subamia; Ni Nyoman Widiasih; I Gusti Ayu Nyoman Sri Wahyuni; Putu Lilik Pratami Kristiyanti (UPT Laboratorium Terpadu, Universitas Diponegoro, 2023)
Problems often occur in sample testing using the FTIR instrument, one of which is that the spectrum quality of the measurement results is not optimal. This has implications for the accuracy of the test results. This condition indicates that the performance of the tool is not optimal. The non-optimal quality of this spectrum is thought to be influenced by the composition factor and the thickness of the sample-KBr which is measured not in accordance with the legibility limits of the instrument. To overcome this problem, it is important to conduct a study to find out the optimum composition and thickness of the KBr-sample which can be measured properly by the instrument. The purpose of this study was to optimize the performance of the FTIR device through a study of the optimum composition and thickness of the KBr-sample so that a good spectrum was produced in the sample measurement using FT-IR type IRAffinity-1 Shimadzu. This research is an experimental research with infrared spectrophotometry method, using the One Shot Case Study design. The treatment is a measurement of the variation in the composition of the sample-KBr and the thickness of the sample. The spectrum resulting from the reading of the FT-IR spectrophotometer is interpreted to include wave number and transmittance percent. The results of the readings of each variation are compared with the standard spectrum to see the optimization of the measurement results so that the best spectrum is obtained. The results showed that the optimum ratio of the sample-KBr composition was 4% and the optimum thickness was 1/2 pan.